Effects of CO2–water–rock cycling cycles on sandstone pore structure - Huang, Hao; Sun, Qiang; Yang, Duoxing; Geng, Jishi; Zhang, Liwei; Pan, Yanning (Frontiers in Energy Research, 2024)
As global CO2 levels increase, the storage of CO2 in saline aquifers is considered a large-scale and cost-effective method for mitigating CO2 emissions. To examine the impact of cyclic CO2 injection on sandstone formations within various saline aquifers, five cyclic injections of differing durations were performed, and the effects of the frequency and duration of CO2 injection cycles on sandstone pore structure were monitored using NMR. Additionally, ICP-OES was employed to assess changes in the TDS and metal ion concentrations in the saline water layer post-injection. The findings reveal that sandstone samples experience structural degradation as a result of cyclic injection. Initially, the proportion of macropores in sandstone samples increases with the number of injections but subsequently decreases. SO4 2-ions exert a more significant influence on the sandstone pore structure compared to Cl -ions. The concentrations of Ca 2+ and Mg 2+ ions in the solution initially rise, followed by a subsequent decline. By integrating the principles of pore structure and considering the formation of crystals through the combination of metal cations and anions, the mechanism underlying the changes in sandstone pore structure due to cyclic injection is elucidated. This study explores the effects of CO2 cyclic injection on reservoir sandstone and evaluates how different saline aquifer types affect pore structure deterioration. The research offers valuable reference points and a foundation for laboratory investigations of underground CO2 storage in saline aquifers.